ANALISIS HUBUNGAN BELANJA HIBAH DAN BANTUAN SOSIAL DENGAN PENDAPATAN MASYARAKAT: STUDI PADA PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Stephanus Eri Kusuma (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This study aims to analyse the relationship between grants and social assistance distributed by the Regional Government of the Special Region of Yogyakarta and the income of people in the region. In this study, the indicators of grants and social assistance used are (1) the total value of grants and social assistance delivered in all forms, (2) the value of grants and social assistance delivered in the form of money, and (3) the value of grants and social assistance delivered in the form of goods and services. Meanwhile, the community income indicator used is the per capita income of the people in Yogyakarta at 2010 constant prices. This research examines the phenomenon of grants and social assistance of the Special Region of Yogyakarta in 2017-2021. The data is obtained directly from the Regional Financial and Asset Management Agency (BPKAD DIY) and data from the Central Statistics Agency for the Special Region of Yogyakarta Province. Data processing utilizes statistical program SPSS 26 to provide correlation analysis and is supported by the utilization of Microsoft Office Excel to provide graphical analysis. The results of the analysis indicate that, statistically, there is a strong, positive and significant relationship between grants (especially grants in total and grants in the form of money) and per capita income of the people of DIY. Meanwhile, statistically, there is no significant relationship between social assistance and per capita income of the people of DIY